PENGGUNAAN KALIMAT IMPERATIF PADA PRODUK KECANTIKAN UNILEVER - Kristiana, Dian (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
About problem which is assessed deep observational it is subject to be know how imperatif's sentence purpose commands on unilever's beauty product and how imperatif's sentence purpose prohibition on unilever's beauty product. This research intent to describe how imperatif's sentence purpose commands and prohibition purpose on Unilever's beauty product. Observational method that is utilized in this research is kualitatif's descriptive method. It becomes research basic because in this research researcher describes imperatif's sentence commands and imperatif's sentence prohibition. Result observationaling to point out that imperatif's sentence purpose on Unilever's beauty product there are many utilize imperatif's sentence commands where a consumer get to do an action or respond is purpose. Say frequent one to be utilized on sentence imperatif is say utilize . Meanwhile imperatif's sentence researcher prohibition just finds 2 prohibition sentence which is avoid and don't.